Teachers’ Affective Well-being and Teaching Experience: The Protective Role of Perceived Emotional Intelligence - Fernández-Berrocal, Pablo; Gutiérrez-Cobo, María J.; Rodriguez-Corrales, Juan; Cabello, Rosario (Frontiers in Psychology, 2017)
Teaching is a highly emotional and demanding profession. Developing emotional well-being among teachers will benefit not only the teachers themselves, but also their students. Previous studies have shown the protective role of emotional intelligence (EI) as well as inconsistencies in the years of teaching experience variable on positive and negative work-specific variables. The aim of the present study was to analyse how EI and years of teaching experience are related to affective well-being in teachers. Further, we analyse the moderator role of perceived EI on the link between level of teaching experience and affective well-being. For these purpose, 524 teachers from different Spanish public schools took part in the study. They first completed the Trait Meta-Mood Scale-24 (TMMS-24) for measuring perceived EI, which evaluates three scales: Attention to one’s Feelings (Attention), Emotional Clarity (Clarity), and Mood Repair (Repair). Secondly, they completed the Positive and Negative Affect Schedule (PANAS) for affective well-being, which measures Positive Affect (PA) and Negative Affect (NA). Finally, teachers indicated their years of teaching experience. The results revealed that teaching experience and attention variables are counterproductive in determining lower PA and higher NA, respectively. Clarity and Repair appeared to be a significant determinant of PA and NA, with higher Clarity and Repair determining higher PA and lower NA. Moderator analyses showed how teaching experience significantly decreased PA in teachers who had average or low levels of Repair, but not for those with higher levels of this variable, emphasizing the important role of Repair as a protector of affective well-being in teachers. Limitations and future areas for research are discussed.